Penerapan Model Pembelajaran Discovery Learning Untuk Meningkatkan Hasil Belajar IPA Siswa Kelas V SD UPT SPF SD Inpres Bertingkat Bara Baraya II Kota Makassar - Tomo S, Arwan; Syawaluddin, Ahmad; Andriany, Mega (Pinisi Journal Pendidikan Guru Sekolah Dasar, 2025)
This research aims to describe the application of the Discovery Learning learning model to improve science learning outcomes in class V students. The approach used is a qualitative approach and a type of Classroom Action Research which consists of 2 cycles. The focus of this research is the application of the Discovery Learning learning model and student learning outcomes. Data collection uses observation, test and documentation formats. The results of the research show that there is an increase in learning both in teacher and student activities and student learning outcomes. The conclusion of this research is that teacher teaching activities and student learning have increased, in cycle I, meetings I and II were in the adequate category (C) while in cycle II, meetings I and II were in the good category (B). Student learning outcomes in cycle I with a percentage of 53.33% were in the poor category (K) while in cycle II with a percentage of 93.33% student learning outcomes had improved and were in the good category (B). The application of the Discovery Learning learning model in science learning can improving the learning outcomes of V students at SD Inpres Bertingkat Bara Baraya II.